THE SPEECH ACT IN DAVID CAMERON’S SPEECH - M.Pd, Merry Rullyanti; S.S, Sunarti (JURNAL LITERARY CRITICISM, 2014)
Speech act is the action or intent that a speaker accomplishes when uses the language in context, the meaning of which is inferred by listener. It is divided into three classification, those are locutionary act, illocutionary act, and perlocutionary act. This thesis explored the speech act in David Cameron’s speech with the purposes to identify contexts underly and which are implied in utterances of the speeh from David Cameron’s speech. The writer used qualitative descriptive method analysis which tried to analyze and to identify every utterance using speech acts. Then the writer will describe the data which will answer two questions in the statement of the problem. Beside that Searle’s theories also used to find some speech act in Cameron’s speech such as representative, commissives, directives, expressive, and declarative. The result of this thesis is there are forty seven illocutionary acts that found in David Cameron’s script of Speech based on Serale theories. It consists of sixteen representatives, nineteen directives, three commissives and nine expressive. To conclude the illocutionary act that found n David Cameron’s speech mostly directives in the context of advice, ordering and question. Keywords: Speech act, David Cameron’s Speech.